Dampak Penggunaan Model Problem Based Learnıng terhadap Kemampuan Berfıkır Kreatıf Sıswa pada Meterı Momentum & Impuls - Siska Luffa Kalkavia; Elisa Elisa; Ngadimin Ngadimin (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
The purpose of this study was to determine the impact of using the problem based learning (PBL) model on students' creative thinking skills on momentum and impulse material. This research was conducted at MAS Darul Ihsan Aceh Besar, on 6 and 8 August 2022. This study used a quantitative approach with an experimental method in the form of Pre Experimental Design in the form of one group pretest posttest design. The population included in this study were students of class X IPA MAS Darul Ihsan Aceh Besar and then taken as a sample with purposive sampling technique, so the sample of this study was class X IPA G as many as 25 students. The instrument used in this study is a test instrument in the form of a description (essay) and non-test in the form of a questionnaire and the instrument used in this study has been tested for validity by experts. Data collection in this study was analyzed using N-Gain for questions and questionnaires were analyzed using the percentage formula. For the N-Gain value, the results were obtained in 3 categories consisting of 13 students in the high category, 9 students in the medium category and 3 students in the low category. And the results of the overall student response to the PBL model are also very good, because students get something new which they have never gotten before.